The Racial Middle : Latinos and Asian Americans Living Beyond the Racial Divide. - O'Brien, Eileen (NYU Press, 2008)
The divide over race is usually framed as one over Black and White. Sociologist Eileen O'Brien is interested in that middle terrain, what sits in the ever-increasing gray area she dubbed the racial middle. The Racial Middle, tells the story of the other racial and ethnic groups in America, mainly Latinos and Asian Americans, two of the largest and fastest-growing minorities in the United States. Using dozens of in-depth interviews with people of various ethnic and generational backgrounds, Eileen O'Brien challenges the notion that, to fit into American culture, the only options availabl.